2014
DOI: 10.1111/ajt.12556
|View full text |Cite
|
Sign up to set email alerts
|

Left Versus Right Lobe Liver Donation

Abstract: The authors historically have been proponents of left hepatectomy (LH) and left lateral segmentectomy (LLS) donation for living donor liver transplantation, and here they retrospectively review 441 liver donors, reporting complications over 15 years (1). Donor complication rates decreased overall during the study period, which they attributed to the cumulative experiences resulting in mastery of both surgical technique and postoperative management. In addition, they describe the introduction of real-time C-arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Our data confirm previous reports that right lobe donation can be performed as safely as left lobe donation [7][8][9][10]. Despite minor biochemical differences, there appears to be no clinically significant difference in donor outcomes between both groups, especially when the middle hepatic vein is left with the donor.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data confirm previous reports that right lobe donation can be performed as safely as left lobe donation [7][8][9][10]. Despite minor biochemical differences, there appears to be no clinically significant difference in donor outcomes between both groups, especially when the middle hepatic vein is left with the donor.…”
Section: Discussionsupporting
confidence: 89%
“…Literature evidence suggests that a cumulative experience with living donors hepatectomies reduces the overall complication rate, particularly for RH. [4,7,[10][11][12][13]. Hwang et al reported that major complications were more in right lobe Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also to considerer is the fact that LDLT is surgically more challenging than whole organ transplantation. Donor major complications, exceeding Clavien's classification grade II, were described in up to 44% after right-lobe LDLT with a mortality risk up to 0.8% [128][129][130]. Donors of right liver lobe experience operating procedures with longer duration, have significant longer hospital stay and require more blood transfusions [131,132].…”
Section: Living-donor Liver Donationmentioning
confidence: 99%